Viral Circular RNAs and Their Possible Roles in Virus-Host Interaction - Zhang, Xing; Liang, Zi; Wang, Chonglong; Shen, Zeen; Sun, Sufei; Gong, Chengliang; Hu, Xiaolong (Frontiers in Immunology, 2022)
Circular RNAs (circRNAs) as novel regulatory molecules have been recognized in diverse species, including viruses. The virus-derived circRNAs play various roles in the host biological process and the life cycle of the viruses. This review summarized the circRNAs from the DNA and RNA viruses and discussed the biogenesis of viral and host circRNAs, the potential roles of viral circRNAs, and their future perspective. This review will elaborate on new insights gained on viruses encoded circRNAs during virus infection.